Environmental Control of Triplet Emission in Donor–Bridge–Acceptor Organometallics. (1st January 2020) - Feng, Jiale; Yang, Lupeng; Romanov, Alexander S.; Ratanapreechachai, Jirawit; Reponen, Antti‐Pekka M.; Jones, Saul T. E.; Linnolahti, Mikko; Hele, Timothy J. H.; Köhler, Anna; Bässler, Heinz; Bochmann, Manfred; Credgington, Dan
Abstract: Carbene‐metal‐amides (CMAs) are a promising family of donor–bridge–acceptor molecular charge‐transfer (CT) emitters for organic light‐emitting diodes. A universal approach is demonstrated to tune the energy of their CT emission. A blueshift of up to 210 meV is achievable in solid state via dilution in a polar host matrix. The origin of this shift has two components: constraint of thermally‐activated triplet diffusion, and electrostatic interactions between guest and polar host. This allows the emission of mid‐green CMA archetypes to be tuned to sky blue without chemical modifications. Monte‐Carlo simulations based on a Marcus‐type transfer integral successfully reproduce the concentration‐ and temperature‐dependent triplet diffusion process, revealing a substantial shift in the ensemble density of states in polar hosts. In gold‐bridged CMAs, this shift does not lead to a significant change in luminescence lifetime, thermal activation energy, reorganization energy, or intersystem crossing rate. These discoveries offer new insight into coupling between the singlet and triplet manifolds in CMA materials, revealing a dominant interaction between states of CT character. The same approach is employed using materials which have been chemically modified to alter the energy of their CT state directly, shifting the emission of sky‐blue chromophores into the practical blue range. Abstract : How to gently tune emission from green to blue? The luminescence of organic emitters can be blueshifted via triplet diffusion and electrostatic interactions with surrounding molecules without chemical modifications while preserving excellent molecular and photophysical properties.